Vowel harmony decay in Old Norwegian - Sandstedt, Jade J. (Papers in Historical Phonology, 2020)
Vowel harmony involves the systematic correspondence between vowels in some domain for some phonological feature. Though harmony represents one of the most natural and diachronically robust phonological phenomena that occurs in human language, how and why harmony systems emerge and decay over time remains unclear. Specifically, what motivates harmony decay and the pathways by which harmony languages lose harmony remains poorly understood since no consistent historical record in any single language has yet been identified which displays the full progression of this rare sound change (McCollum 2015, 2020; Kavitskaya 2013, Bobaljik 2018). In this paper, I explore the progression and causation of vowel harmony decay in Old Norwegian (c 1100–1350). Using a grapho‐phonologically tagged database of a sample of 13th‐ to 14th‐century manuscripts, I present novel corpus methods for tracking and visualising changes to vowel co‐occurrence patterns in historical records, demonstrating that the Old Norwegian corpus provides a consistent and coherent record of harmony decay. The corpus distinguishes categorical pre‐decay harmony, probabilistic intermediate stages, and post‐decay non‐harmony. Across the Old Norwegian manuscripts, we observe a variety of pathways of harmony decay, including increasing harmony variability via the collapse of harmony classes introduced by vowel mergers, the lexicalisation of historically harmonising morphemes, and trisyllabic vowel reductions which limit harmony iterativity. This paper provides the first detailed corpus study of the full spectrum and causation of this rare sound change in progress and provides valuable empirical diagnostics for identifying and analysing harmony change in contemporary languages.